Using Fourier Transform Infrared Spectroscopy to Study Effects of Magnetic Field Treatment on Wheat (Triticum aestivum L.) Seedlings - Zhenlin Wei; Dejie Jiao; Junxiao Xu (Journal of Spectroscopy)
Magnetic field treatments have been utilized to promote germination and growth of a variety of species of plants; however the mechanism of concern has not been fully elucidated. In this research, wheat seedlings were treated with 500 mT and 1500 mT static magnetic field (SMF) for 10 and 20 min, respectively. Analyzing Fourier transform infrared spectra collected from leaves of seedlings showed that SMF treatments decreased the contents of lipids and proteins, shifted bands to higher wavenumbers in 3000–2800 cm−1 regions, and increased the ratio of CH2/CH3 which likely indicates a structural variation of lipids. For bands assigned to different second structures of proteins, slight bands shifting and changing the ratio of different second structures of proteins were observed due to SMF treatments. To summarize, the results revealed that lipids rather than proteins were sensitive to SMF treatments. The results provided insight into the SMF induced conformational changes of lipids and proteins in wheat leaves, which will help elucidate the biological mechanisms of SMF on plant growth and development.